2010
DOI: 10.3899/jrheum.091110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Genes Encoding RANK, RANKL, and OPG in Rheumatoid Arthritis: A Case-Control Study

Abstract: The minor allele of the RANK SNP rs35211496 may be protective against RA, while the minor alleles of the RANKL SNP rs2277438 may increase susceptibility to RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
(19 reference statements)
1
29
3
3
Order By: Relevance
“…However, the RA group showed significantly higher serum levels of RANKL, a higher RANKL/OPG ratio, and a lower serum level of OPG than the controls in the study. A German article also reported that OPG rs3102735 T/C and rs2073618 G/C polymorphisms showed no significant difference between patients with RA and healthy controls in a Caucasian population (Assmann et al, 2010). Thus, it appears that OPG rs3102735 T/C and rs2073618 G/C polymorphisms are not associated with the risk for RA in Asian or Caucasian populations, indicating that the correlation between the two SNPs and RA may not be associated with ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the RA group showed significantly higher serum levels of RANKL, a higher RANKL/OPG ratio, and a lower serum level of OPG than the controls in the study. A German article also reported that OPG rs3102735 T/C and rs2073618 G/C polymorphisms showed no significant difference between patients with RA and healthy controls in a Caucasian population (Assmann et al, 2010). Thus, it appears that OPG rs3102735 T/C and rs2073618 G/C polymorphisms are not associated with the risk for RA in Asian or Caucasian populations, indicating that the correlation between the two SNPs and RA may not be associated with ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs in the RANKL gene and the OPG gene, which might influence the binding of transcription factors, have been reported to be significantly associated with bone metabolism and susceptibility to RA (Kim et al, 2007;Assmann et al, 2010). The OPG gene encodes a known regulator of bone remodeling and maintains a fine balance between bone formation and resorption, involving osteoblasts and osteoclasts, and thus potentially contributes to the pathophysiology of osteoporosis (Simonet et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study implied some role in longevity [45]. Other studies examining femoral neck compression strength [46], susceptibility to rheumatoid arthritis [47], or breast cancer [48] did not see any association.…”
Section: Discussionmentioning
confidence: 99%